Effect of home exercise on prevention and treatment of lymphedema in breast cancer patients - Yin, Hui; Wu, Weiwei; Zhang, Qungui; Xie, Fangfang (Frontiers in Oncology, 2025)
ObjectiveTo develop a systematic home exercise intervention program based on the Expert Consensus on Home Exercise for Prevention and Treatment of Lymphedema in Postoperative Breast Cancer Patients and evaluate its effectiveness in preventing and treating lymphedema in breast cancer patients, thereby improving their home-based quality of life.MethodsA pre–post controlled study was conducted involving 104 breast cancer patients who underwent surgery at Ganzhou Cancer Hospital between November 2024 and May 2025. Participants were chronologically assigned to a control group (n = 52, receiving routine care) or an experimental group (n = 52, receiving routine care plus a consensus-based systematic home exercise intervention). The intervention, delivered by a multidisciplinary team, included assessment of exercise contraindications, evaluation of lymphedema status, exercise capacity testing, and implementation of resistance training, flexibility exercises, aerobic exercise, deep breathing exercises, and self-manual lymphatic drainage.ResultsThe incidence of lymphedema was significantly lower in the experimental group (7.69%) than in the control group (34.62%), with an absolute risk reduction of 26.92% (95% CI: 12.51% to 41.33%). The experimental group also demonstrated significantly greater improvement in the Disabilities of the Arm, Shoulder, and Hand (DASH) score (mean difference = −12.90 points; 95% CI: −15.80 to −10.00) and the Functional Assessment of Cancer Therapy-Breast (FACT-B) score (mean difference = +13.30 points; 95% CI: 10.49 to 16.11). Exercise compliance was significantly higher in the experimental group (96.15% vs. 78.85%).ConclusionThe consensus-based systematic home exercise intervention effectively reduced lymphedema incidence, improved upper limb function, and enhanced quality of life in breast cancer patients. The program demonstrates high clinical feasibility and is recommended for wider application. Future multi-center randomized controlled trials are warranted to further validate its long-term benefits.